Potencial do crambe para o manejo de nematoide das lesões radiculares e das galhas na cultura da soja - Silva, Carolina Amaral Tavares da (2015)
The crambe (Crambe abyssinica Hochst) is an oleaginous plant of short cycle that can be cultivated in succession with soybean (Glycine max (L.) Merrill), in a profitable way, in the winter crop. Soybean is one of the most important crops in Brazil. However, its production can be limited by some factors, e.g. the presence of nematodes Meloidogyne javanica and Pratylenchus brachyurus. Alternative soil management systems were considered to control these pathogens, including organic matter addition and crop rotation or succession with species resistant to or antagonists of nematodes. Therefore, the present study aimed to assess the potential of crambe in the management of M. javanica and P. brachyurus in soybean crop. Experiments were conducted to assess the susceptibility of crambe to M. javanica, the introduction of the oilseed plant in the crop succession system aimed to reduce the population of M. javanica and P. brachyurus, the use of crambe meal in the control of M. javanica and P. brachyurus and the effect of extract obtained from the aerial part (shoot) of crambe on the embryonic development of M. javanica. The crambe plant was susceptible to M. javanica, with high reproduction rates of these pathogens. The vegetative parameters and grain oil content were not affected by parasitism, unlike yield and grain mass that were reduced in the presence of root-knt nematodes. The introduction of crambe in the crop succession system was found to be effective in controlling P. brachyurus, and the reproduction rates of M. javanica were lower for crambe compared to other succession systems. The application of crambe meal to pots planted with soybean showed reduction in the populations of M. javanica and P. brachyurus, and had a positive influence on soybean vegetative development. The embryonic development of M. javanica was not affected by exposure to the aqueous extract, and the number of hatched juveniles of M. javanica was lower at the concentration of 300 ppm of the aqueous extract, and was not influenced by the methanolic extract